Coaching – moda czy konieczność? Możliwości zastosowania coachingu w bibliotece - Dąbrowicz, Małgorzata (Biblioteka Uniwersytecka w Poznaniu, 2017)
W artykule przedstawiono coaching jako popularną obecnie drogę rozwoju osobistego i zawodowego, a także metodę zarządzania ludźmi oraz zespołami pracowniczymi. Zaprezentowano wybrane definicje coachingu, ujmując go na tle innych form rozwoju pracowników, oraz wielość istniejących szkół i odmian coachingu. Ukazano jego różne formy i możliwości ich zastosowania w bibliotece, ze szczególnym uwzględnieniem coachingu menedżerskiego. Wskazując na korzyści płynące z coachingu dla jednostki, zespołu oraz całej instytucji, podkreślono potrzebę i znaczenie tworzenia kultury coachingowej w bibliotece.

Abstract. this article explores the possibilities of coaching as a currently popular way of internal personal and professional development as well as an effective and useful tool in human resources and work teams management. a number of selected definitions of coaching are discussed and presented against the background of other forms of professional development of staff personnel and the present multiplicity of existing schools and varieties of coaching. the latter’s different forms and possibilities that are offered in their applications in a library are then discussed, with special attention given to managerial coaching. while indicating the advantages of coaching vis a vis an individual worker, team or the entire institution, the author emphasizes the need for and significance of creating a coaching culture in libraries.
Coaching – just another fashionable trend or a necessity? Possibilities of coaching application in the library
Keywords: coaching; coaching menedżerski; coaching zespołowy; rozwój osobisty; rozwój zawodowy; metody zarządzania; zarządzanie ludźmi; kultura coachingowa; managerial coaching; collective (team) coaching; personal development; professional development; management methods; human resources management; coaching culture